2018
DOI: 10.1007/s10570-018-1902-4
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of wood-biopolymers into macrofibers with tunable surface energy via dry-jet wet-spinning

Abstract: Surface chemistry of regenerated all-wood-biopolymer fibers that are fine-tuned by composition of cellulose, lignin and xylan is elucidated via revealing their surface energy and adhesion. Xylan additive resulted in thin fibers and decreased surface energy of the fiber outer surfaces compared to the cellulose fibers, or when lignin was used as an additive. Lignin increased the water contact angle on the fiber surface and decreased adhesion force between the fiber cross section and a hydrophilic probe, confirmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 35 publications
4
21
0
Order By: Relevance
“…This deviation confirms that the optimum spinning conditions can vary depending on the type of biopolymer or biopolymer blend dissolved in the IL. 39 , 40 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This deviation confirms that the optimum spinning conditions can vary depending on the type of biopolymer or biopolymer blend dissolved in the IL. 39 , 40 …”
Section: Resultsmentioning
confidence: 99%
“…The decrease in the tenacity of Ioncell cellulose fibers with the incorporation of additives, such as lignin and xylan, has been reported previously. 25 , 40 With the addition of 10 wt % organsolv and kraft lignin, the tenacity of the cellulose fiber decreased by 12 and 8%, respectively. 25 At 20 wt % xylan and lignin, the tenacity decreased even by 26 and 32%, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lignin can serve as a precursor for CF production and can be used as single raw material or blended with other polymers, such as PAN (B. Zhang et al, 2019), nanocellulose (Wang et al, 2019), cellulose (Bengtsson et al, 2018;Ma et al, 2015) as well as a mixture of cellulose and hemicellulose (Nypelö, Asaadi, Kneidinger, Sixta, & Konnerth, 2018).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…on the structure and mechanical properties of lignin/cellulose precursor fibers and carbon fibers have been investigated systematically [ 139 , 155 , 156 , 157 ], from which it is concluded that the cellulose constituent dominates precursor fiber structure and mechanical performance. Increasing lignin content decreases fiber strength due to the disturbance of oriented cellulose crystallites [ 141 , 158 , 159 ] and increases carbon yield [ 160 ] due to lignin’s carbon-rich structure. However, the draw ratio of solution-spun lignin/cellulose precursor fibers seemed to have no significant influence on the carbon fiber’s physical properties [ 155 ], although the detailed reasons from the perspective of fiber structure were not revealed.…”
Section: Mechanical Performance Of Lignin-based Fibersmentioning
confidence: 99%